2019
DOI: 10.1080/1331677x.2019.1696691
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of institutional quality and business environment on Chinese foreign direct investment flow to African countries

Abstract: This study examines the impacts of institutional quality and business environment on Chinese foreign direct investment (F.D.I.) flow to Africa. We derive aggregate indicators of institutional quality and business environment using economic and governance institutions, doing business, transport efficiency indicators conducting a principal component analysis. We employ Poisson pseudo-maximum likelihood (P.P.M.L.) procedure to estimate the gravity model of F.D.I. flow as it can solve zero-valued observations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 32 publications
(35 reference statements)
2
16
0
Order By: Relevance
“…Babecky et al, 2013;Cevik et al, 2016;David & Grobler, 2020;Sare et al, 2019). Borojo and Yushi (2020) contended that owing to the introduction of numerous economic measures and reforms in the last decades, African countries have opened and harmonized financial markets, whereby the capitalization of the 10 largest African financial markets tripled from 2002 to 2008. Boako et al (2016) asserted that net private capital flows to Sub-Saharan African countries doubled between 2010 and 2012 in comparison with the period 2000-2007, whereas the portfolio and cross-border bank flows into Sub-Saharan African markets exceeded the US$17 billion in 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Babecky et al, 2013;Cevik et al, 2016;David & Grobler, 2020;Sare et al, 2019). Borojo and Yushi (2020) contended that owing to the introduction of numerous economic measures and reforms in the last decades, African countries have opened and harmonized financial markets, whereby the capitalization of the 10 largest African financial markets tripled from 2002 to 2008. Boako et al (2016) asserted that net private capital flows to Sub-Saharan African countries doubled between 2010 and 2012 in comparison with the period 2000-2007, whereas the portfolio and cross-border bank flows into Sub-Saharan African markets exceeded the US$17 billion in 2012.…”
Section: Introductionmentioning
confidence: 99%
“…A well-functioning institutional environment also influences the inflow of foreign direct investment. Research conducted by Borojo and Yushi (2020) confirmed that the improvement of the quality of the business and institutional environment of African countries stimulates the inflow of Chinese FDI to Africa. Additionally, Ascani et al (2016), using data on 6888 greenfield investment projects, proved that the national institutional framework quality is beneficial for attracting foreign investment.…”
Section: Results and Discussion Of Findingsmentioning
confidence: 94%
“…As cited by reference [21], the 10 doing business indicators further decomposed into the number of steps it required, number of working days, the number of official costs, and minimum capital required in starting a business, registrations of firms, and dealing with firm constructions permits. The finding by reference [25] also adds that the scores from each of doing business indicators are worthful credentials in multinational firms' growth and sustainability responses in addition to traditional FDI determinants. In a similar manner [26], cross-border investors prefer frontiers, a top-ranked and stable economy.…”
Section: Introducing Ease Of Doing Business In Multinational Enterpri...mentioning
confidence: 90%